Evaluation of Acute Nonlymphocytic Leukemia and Its Subtypes With Updated Benzene Exposure and Mortality Estimates: A Lifetable Analysis of the Pliofilm Cohort. Issue 4 (April 2016) - Rhomberg, Lorenz; Goodman, Julie; Tao, Ge; Zu, Ke; Chandalia, Juhi; Williams, Pamela R.D.; Allen, Bruce
Abstract : Objective: US Environmental Protection Agency (EPA) based its benzene carcinogenicity assessment on the Pliofilm cohort. We evaluated associations between benzene exposure and acute nonlymphocytic leukemia (ANLL) and acute myelocytic leukemia (AML) risks using this cohort's updated exposure estimates and mortality data. Methods: We calculated standardized mortality ratios (SMRs) for ANLL/AML using lifetable analyses, with various exposure quantile categories and lag times. Results: Workers in the highest exposure categories had significantly elevated risks of ANLL and AML; no leukemia cases occurred in lower exposure categories. Exposure within 10 years of cancer onset appears most relevant for leukemia induction. Conclusions: Our results confirmed the association between high-level benzene exposures and leukemia risks, and provided further evidence of a threshold effect and relevant exposure window. Our findings call for an updated risk assessment for benzene carcinogenicity using updated exposure estimates and mortality data.